Evaluation of genetic variability in Symplocos laurina Wall. from two biodiversity hotspots of India - Bhagwat, Rasika M.; Banu, Sofia; Dholakia, Bhushan B.; Kadoo, Narendra Y.; Lagu, Meena D.; Gupta, Vidya S. (Plant Systematics and Evolution, 2014)
Symplocos laurina Wall., an important medicinal tree species, is one of the pioneering plants for establishment of shola forest ecosystem. We analyzed 208 accessions of S. laurina from 13 populations belonging to three ecoregions in India namely, Western Ghats, Eastern Ghats and Northeast India, to comment on the genetic diversity and population structure of the species. Of the 100 inter simple sequence repeat primers screened, eight were selected based on their clear and reproducible polymorphic patterns. These eight ISSR primers produced on an average 1,014 bands from 208 accessions, of which 6.58 % were rare bands, 55.96 % were shared bands and 37.46 % were similar bands. The primers, UBC835 and UBC880, amplified the highest number of polymorphic loci (16), while the primer UBC852 amplified the least number of amplicons (9). The values for total genetic diversity (H-T) and the average heterozygosity (H-S) were 0.3407 and 0.2263, respectively; while the coefficient of genetic differentiation (G(ST)) was 0.3358. Within-population variance was higher (68 %) than among-population variance (17 %), indicating high intra-population genetic diversity. These populations were grouped according to their geographical location in cluster analysis. Mantel test also showed significant positive correlation between genetic and geographical distances. The present study revealed the importance of the Palghat gap in South India in shaping the distribution of genetic diversity in S. laurina.
Keywords: Biodiversity hotspots; Genetic diversity; ISSR; Palghat gap; Symplocos laurina

Expanding the Egbenema horizon: Novel species discovery in India and first complete genome assembly of the genus - Bhagat, Jayesh M.; Khilari, Ajinkya A.; Shanmugam, Dhanasekaran; Patankar, Meena (Algal Research-Biomass Biofuels and Bioproducts, 2025)
The recognition of Egbenema bharatensis, a novel species of cyanobacteria from the Northern Western Ghats, extends the ecological and phylogenetic understanding of the genus Egbenema and highlights terrestrial microbial diversity of the region. Morphological characterization revealed resemblance with other Egbenema species but was inconclusive for definitive taxonomic classification. Preliminary phylogenetic analysis based on 16S rRNA gene sequences indicated affiliation with the genus but showed less than 98 % similarity to known species, pointing toward taxonomic distinctiveness. Analysis of the 16S-ITS region further supported this differentiation, revealing unique secondary structural features. Based on these findings, we propose the isolate as a novel species within Egbenema. Whole-genome sequencing provided full resolution and functional genome annotation revealed nitrogen fixation, cobalamin biosynthesis, and stress tolerance pathways, suggesting its metabolic versatility and potential biotechnological applications. The presence of multiple toxin-antitoxin systems also reflects its adaptability to environmental fluctuation. This study also presents the first complete genome of the genus Egbenema, filling a significant gap in cyanobacterial genomic resources. These findings encourage integrative taxonomic practices and affirm the significance of exploring biodiversity hotspots for uncovering cryptic microbial diversity with ecological and industrial potential.
Keywords: 16S rRNA; Biodiversity hotspots; Cyanobacteria; Egbenema bharatensis; ITS secondary structure; Northern Western Ghats; whole-genome sequencing